Paradoxes of the democratization of higher education - Youn, Ted I. K. (Research in social problems and public policy, 2016)
Research in Social Problems and Public Policy (RSPPP) is a peer-reviewed series devoted to the sharpening and reshaping of scientific discourse involving the intersection of social problems and public policy. In particular, it is interested in the analysis of the potential failure of public institutions to fulfil their obligations to the broader society. Multidisciplinary in nature, Research in Social Problems and Public Policy presents important themes of: social/crime problems and their treatment; criminal justice; law and public policy; crime, deviance and social control; courts and diversion programs; therapeutic jurisprudence, restorative justice and alternative dispute resolution; law and society; substance use/abuse and treatment; health and society; and institutional interaction. The articles have a clear connection to the series' main focus, lying at the confluence of social problems and public policy. This volume focuses on the democratization of higher education.